The Relationship between Phosphatidyl-inositol-3-kinase (PI3K) and Mammalian target of rapamycin (MTOR) mRNA Expression with Lymphovascular Invasion and Ipsilateral Lymph Node Metastasis in Triple-Negative Operable Breast Cancer - Wahid, Dian Ibnu; Wahyono, R. Artanto; Setiaji, Kunta; Hardiyanto, Herjuna; Suwardjo, Suwardjo; Anwar, Sumadi Lukman; Aryandono, Teguh; Irianiwati, Irianiwati (Asian Pacific Journal of Cancer Nursing, 2026)
Background: Triple Negative Breast Cancer (TNBC) is an aggressive subtype of breast cancer characterized by high proliferation, early metastasis, and poor prognosis. The phosphatidylinositol-3-kinase (PI3K)/mammalian target of rapamycin (mTOR) signaling pathway regulates cell proliferation, migration, and invasion, and may play a role in lymphovascular invasion (LVI) and lymph node metastasis. Understanding its role may provide insight into the metastatic potential of TNBC and identify potential biomarkers for prognosis and therapy. Objective: To analyze the relationship between PI3K and mTOR mRNA expression with lymphovascular invasion and ipsilateral axillary lymph node metastasis in operable TNBC patients. Methods: This was an observational analytic cross-sectional study using secondary data from operable TNBC patients treated at Dr. Sardjito General Hospital, Yogyakarta. A total of 54 samples met the inclusion criteria. The relationships between PI3K/mTOR expression, LVI, and lymph node metastasis were analyzed using Chi-square and Fisher’s exact tests, with p < 0.05 considered statistically significant. Result: High PI3K expression was observed in 50 patients (92.6%), while high mTOR expression was found in 46 patients (85.2%). Lymphovascular invasion was positive in 48 patients (88.9%), and ipsilateral lymph node metastasis occurred in 41 patients (75.9%). High PI3K expression showed a significant association with LVI (p = 0.010) and lymph node metastasis (p = 0.013). Similarly, high mTOR expression was significantly associated with both LVI (p < 0.001) and lymph node metastasis (p < 0.001). Multicollinearity testing showed no significant interaction between PI3K and mTOR (VIF = 1.298; tolerance = 0.770), indicating independent effects. Conclusion: High PI3K and mTOR mRNA expression are significantly associated with lymphovascular invasion and ipsilateral lymph node metastasis in operable TNBC, supporting their role in tumor aggressiveness and metastatic potential. These findings suggest that PI3K and mTOR could serve as prognostic biomarkers and potential therapeutic targets in TNBC management.